Scaling of the Granulation Process in the Conditions of GMP Training Center and Assessment of Possible Risks - O. N. Abrosimova; M. A. Burakova (Разработка и регистрация лекарственных средств)
Introduction. The stage of wet granulation is often used in the technology of solids. The method of wet granulation in a mixer-granulator with high shear force can be regarded as the most complicated method of its implementation from the engineering and technological point of view. The mixer-granulator has two mixers located in mutually perpendicular planes. Using an impeller, dry components are mixed, and the chopper, turning on when spraying a humidifier, ensures the formation of granules. By setting different chopper rotational speed, granules of different sizes can be obtained. This granulator has the following advantages: it provides a high product yield (≥ 99 %), takes up small workspaces, and the closed design ensures environmental protection.Aim. The aim of the research is to scale the granulation process, on the example of the solids production technology, using the wet granulation stage - in a mixer-granulator with high shear force.Materials and methods. Dry extract «N» and auxiliary substances were used as a pharmaceutical substance: lactose monohydrate, microcrystalline cellulose (MCC) (MICROCEL® MC-102), potato starch, povidone (Plasdone™ K-29/32), calcium stearate. Granulate under scaling conditions was produced in a mixer-granulator with high shear force. Technological properties of dry extract «N» and granulate were determined by the methods described in National pharmacopeia XIV.Results and discussion. On the basis of experimental studies, it was found that the resulting granulate, both when obtained under laboratory conditions and under scaling conditions, has good flowability, and also has a homogeneous fractional composition. The presence of a grinder in the mixer-granulator made it possible to obtain a more uniform fractional composition of the granulate. A 10-fold increase in loading did not affect the composition of the granulate. When scaling the pelletizing process, a risk analysis was carried out, factors influencing the technological process were identified and structured. It turned out that the most important stages are mixing and the actual granulation. To obtain a homogeneous mixture, additional equipment was used - a mixer.Conclusion. As a result of scaling up the granulation process, the parameters of wet granulation in the mixer-granulator (optimal loading, impeller and grinder rotation frequency), technological properties of the resulting granulate, and risks affecting the technological process were selected. were evaluated and a causal diagram (Ishikawa diagram) was drawn.